The Effect Of Easy And Benefits Of Use Of Technology In Palm Oil Production On Employee Performance (Case Study PT Mahkota Group Tbk) - Yosephine Grace (Citakonsultindo, 2023)
This research aims to analyze the influence of the ease and usefulness of using information technology on employee performance at PT Mahkota Group TBK, a palm oil production company. Data was collected through a questionnaire distributed to 60 respondents who were company employees. The results of the analysis show that the ease and usefulness of information technology has a significant positive influence on employee performance. Hypothesis testing and coefficient of determination also support these findings. In conclusion, company management can improve employee performance by ensuring ease and usefulness in the use of information technology.